Long-term outcomes of aortic valve repair in children with congenital heart disease and their predictors - Z. M. Abdurakhmanov; I. N. Yemets (Российский кардиологический журнал, 2020)
Aim. To retrospectively analyze the long-term results of primary aortic valve repair (AVR) in children.Material and methods. The study included 163 patients operated on from 2004 to 2019. The mean age was 9,58±9,3 years. The patients underwent commissurotomy, decalcification, raphe resection, Trusler technique, raphe shaving, free margin plication, leaflet replacement, leaflet extension, subcommissural annuloplasty, valve sparing aortic root replacement and neocuspidization. Primary endpoint was a composite outcome of freedom from reoperation, recurrent greater than moderate aortic regurgitation, stenosis, whereas secondary — overall survival.Results. The indications for the procedure were stenotic, regurgitant or mixed defect in 80 (49,1%), 38 (23,3%), and 45 (27,6%) patients, respectively. The 10-year survival rate was 99,4%. The mean follow-up was 3,6±1,8 years. Freedom from reoperation, recurrent moderate and greater aortic regurgitation, stenosis at 1,5 and 7 years was, 95%, 70% and 47%, respectively. In multivariate analysis, Trusler technique, leaflet extension, raphe shaving, use of patch, leaflet retraction, complexity of repair were predictors for composite outcome.Conclusion. Reconstruction of aortic valve in children is effective and safe. Avoidance of predictors may significantly improve the long-term results of aortic valve repair.